GAMBARAN PELAKSANAAN PELAYANAN KESEHATAN ESENSIAL DI PUSKESMAS II DENPASAR BARAT PADA MASA PANDEMI COVID-19 - Ni Made Putri Widiantari; Luh Putu Sinthya Ulandari (ARCHIVE OF COMMUNITY HEALTH, 2022)
In the COVID-19 pandemic condition, the health center must be able to adapt and innovate in the provision of services so that they can be given to the maximum for the community. The purpose of this study was to describe the implementation of essential health services at the Puskesmas II Denpasar Barat during the COVID-19 pandemic. Qualitative descriptive research design with in-depth interview data collection techniques. There were 19 informants who were selected based on purposive sampling technique. Data analysis used is data reduction, data presentation, and verification. The results of this study describe based on a financial perspective, namely doing budget planning according to program achievement data, refocusing funds, and shifting the budget in the RKA. Based on a customer perspective is the addition and sterilization of infrastructure, use of PPE, service according to SOP, timely service, cross-sectoral coordination, training, and establish good communication with customers. Based on a internal business process perspective is innovation in the form of online services, providing additional assignments, establishing schedules, adding health workers, changing service mechanisms through screening and implementing health protocols, and handling customer complaints. Based on a growth and learning perspective is the provision of incentives, penalties and sanctions, opportunities to do new jobs related to handling COVID-19, speed of employee information systems, and periodic empowerment and alignment. Keywords: Essential Health Services, Primary Health Care, Balanced Scorecard